Prevention of Antigen-Induced Bronchial Hyperreactivity and Airway Inflammation in Sensitized Guinea-Pigs by Tacrolimus - J. R. Lapa e Silva; C. Ruffié; J. Lefort; M-A. Nahori; B. B. Vargaftig; M. Pretolani (Hindawi Limited, 1999)
We examined the effect of the immunosuppressive agent, tacrolimus (FK506), on antigen-induced bronchial hyperreactivity to acetylcholine and leukocyte infiltration into the airways of ovalbumin-challenged guinea-pigs. Subcutaneous injection of 0.5 mg/kg of FK506, 1 h before and 5 h after intra-nasal antigen challenge prevented bronchial hyperreactivity to aerosolized acetylcholine, eosinophilia in bronchoalveolar lavage (BAL) fluid and bronchial tissue and the invasion of the bronchial wall by CD4+ T-lymphocytes. FK506 also suppressed ovalbumininduced increase in the number of leukocytes adhering to the pulmonary vascular endothelium and expressing α4-integrins. Inhibition by FK506 of antigen-induced bronchial hyperreactivity in sensitized guinea-pigs may thus relate to its ability to prevent the emergence of important inflammatory components of airway inflammation, such as eosinophil accumulation, as well as CD4+ T-lymphocyte infiltration into the bronchial tissue.